Healthcare providers perspectives on home blood pressure management in Peru and Cameroon: Findings from the BPMONITOR study - Tala Al-Rousan; Mina Awad; M. Amalia Pesantes; Namratha R. Kandula; Mark D. Huffman; J. Jaime Miranda; Rafael Vidal-Perez; Anastase Dzudie; Cheryl A.M. Anderson (Preventive Medicine Reports, 2023)
Home blood pressure management, including self-monitoring and medication self-titration, is an efficient and cost-effective tool. Although its use is increasing globally, little is known about the feasibility of such interventions in low and middle-income countries. Further, the perspectives and experiences of healthcare providers who play a big role in ensuring the success of home blood pressure management interventions have not been documented. This qualitative study was conducted with a total of 35 healthcare providers (60% female, mean [SD] age = 37.3 [6.9 years] years), through 4 in-depth interviews from Peru, and 8 in-depth interviews and 4 focus groups from Cameroon. Study participants (healthcare providers) include physicians (primary care physicians), specialists (cardiologists and geriatricians), and nurses that were purposively recruited from two hospitals in two of the largest cities in both countries. Results were thematically analyzed by two researchers. Themes derived were related to feasibility and acceptability, and largely reflected providers in both countries endorsing home blood pressure management. Providers’ concerns were in three main areas; 1) safety of patients when they self-titrate medications, 2) resources such as healthcare financing, local hospital policies that support communications with patients for home blood pressure management, and 3) sustainability through patient adherence, incorporating home blood pressure management within clinical guidelines and hospital policies, and complementing with continued health education and lifestyle modifications. According to providers, home blood pressure management may be feasible and acceptable if tailored multi-faceted protocols were introduced bearing in mind local contexts.